THE DEVELOPMENT OF GAMELAN LEARNING MEDIA FOR ANDROID OPERATING SYSTEM - Yudana, Nisa Puspaningtyas; Wahyono, Sugeng Bayu (Indonesian Journal of Curriculum and Educational Technology Studies, 2019)
Gamelan is one of the most important traditional music instruments of Javanese culture, but it is too expensive for schools to have it. In order to enhance student awareness, sense of belonging and skills on playing Gamelan, this research tried to develop a learning media for Android operating system. By employing research and development (R & D) approach the development process of this research refers to Alessi & Trollip (2001). Adobe flash has been used as a basis of the media development and after several process (planning, design, and development) the learning media is ready to use, because the post-test indicated an increased student score on their understanding and beginner skills on playing Gamelan. At least, this learning media become an alternative way to learn Gamelan traditional music instrument by using Android. Abstrak Gamelan merupakan salah satu instrumen musik tradisional yang paling penting dari budaya Jawa, tetapi terlalu mahal bagi sekolah untuk memilikinya. Untuk meningkatkan kesadaran siswa, rasa memiliki dan keterampilan bermain Gamelan, penelitian ini mencoba mengembangkan media pembelajaran untuk sistem operasi Android. Dengan menggunakan pendekatan penelitian dan pengembangan (R&D) proses pengembangan penelitian ini mengacu pada metode yang dikembangkan oleh Alessi & Trollip (2001). Berikutnya, Adobe Flash telah digunakan sebagai dasar pengembangan media dan setelah beberapa proses (perencanaan, desain, dan pengembangan) media pembelajaran ini siap untuk digunakan, hal itu karena hasil post-test menunjukkan peningkatan skor siswa pada pemahaman dan keterampilan mereka sebagai pemain pemula dalam memainkan Gamelan. Setidaknya, media pembelajaran ini menjadi cara alternatif untuk mempelajari alat musik tradisional Gamelan dengan menggunakan Android.